Ontario Agriculture in the 1910s: The Move Toward Regional Specialization in Crop Production - Bowley, Patricia (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1996)
ABSTRACTUntil the beginning of the 1910s, mixed farming was the most common type of agriculture in Ontario and was based on "self-subsistence": the farm family produced as many of the essentials of life as possible and traded for the other things they needed. During the decade 1910-1920, specialization was recognized as the most practical way to earn a comfortable living at farming. There were two important reasons for this move: the recognition that all crops were not adapted to each climatic and geographic region of Ontario; and the desire to farm according to the principles of soil conservation or "good farming" while still maximizing profits. The Ontario Department of Agriculture in conjunction with the Ontario Agricultural College at Guelph was very active in conducting research and extension work. Through these programs, farmers were able to choose the particular crops and soil management systems which were the best for them.